The Effects of Openness of Internal Reporting and Shared Interest with an Employee on Managerial Collusion and Subsequent Cooperation* - Way, Dan (Contemporary Accounting Research, 2022)
ABSTRACT Collusion between managers who share private information represents a significant control concern for firms. Prior research suggests that mutual monitoring contracts that incentivize honest reporting do not prevent all collusion, making it important to understand how elements of the control environment may facilitate collusion, as well as how control choices—and collusion itself—affect subsequent behavior within the firm. Results of two experiments show that the frequency of collusion between managers in a repeated‐interaction setting is greatest when one can view the other's reports before making their own (“open internal reporting”) and slack obtained from misreporting is shared with a non‐reporting employee (“shared interest”). Moreover, although open (versus closed) internal reporting increases collusion in a single‐shot setting with or without a residual claimant to managers' budget reports being present, neither openness alone nor shared interest alone increases collusion in a repeated‐interaction setting. Results further suggest that collusion improves managers' perceptions of autonomy and group identification, resulting in greater cooperation on a subsequent task and potentially reducing the costs of some collusion to the extent such cooperation benefits the firm. Finally, open internal reporting worsens managers' perceptions of autonomy and group identification which, for managers who did not previously engage in collusion, leads to less cooperation on a subsequent task. In total, these results highlight to firms that the costs of collusion in repeated‐interaction settings frequently found in practice may be greatest when the common control choices of open internal reporting and shared interest are made in tandem, and that open internal reporting may carry another unintended cost in the form of lower cooperation on other tasks.